Modern Methods of Odontopreparation for MetalCeramic for Beginner Prosthodontists - Akhmadov Inomjon Nizomitdin (Genius Journals, 2023)
The paper describes modern ideas about the preparation of teeth. Theoretical foundations and practical methods for achieving the best marginal fit of a metal-ceramic crown are presented. Various aspects of odontopreparation for crowns are described. The paper presents a technique for preparing teeth.
Keywords: odontopreparation; preparation without ledge; round ledge